2014
DOI: 10.1057/ap.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between issues and an individual’s left–right orientation

Abstract: The major body of the literature about individuals' left-right orientation assumes that individuals' values and attitudes towards different issues will, besides other factors, determine their position in the left-right dimension. Regarding values, it is assumed that these are stable over (a long period of) time and hence, affect individuals' left-right orientation. But as issue preferences change over time, cross-nationally and in their importance for individuals, the relationship between issues and left-right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…economic liberalism, monoculturalism). In case of conflicting issue positions in terms of left-right, left-right identification can be adapted based on the issues most salient to the voter (Weber and Saris 2015). Left-right is thus meaningful even if there is a pluralization of issues it is associated with.…”
Section: Resultsmentioning
confidence: 99%
“…economic liberalism, monoculturalism). In case of conflicting issue positions in terms of left-right, left-right identification can be adapted based on the issues most salient to the voter (Weber and Saris 2015). Left-right is thus meaningful even if there is a pluralization of issues it is associated with.…”
Section: Resultsmentioning
confidence: 99%
“…Still, both economic and socio-cultural issues are correlated with left-right, so that support for redistribution and multiculturalism are left-wing attitudes, while economic liberalism and monoculturalism are associated with the right. In case a citizen holds conflicting issue positions in terms of left-right, it is likely that left-right identification is adapted based on the dimension that is most salient to the citizen (Weber and Saris, 2014). Left-right thus remains meaningful, even if there is a pluralization of issues it is associated with.…”
Section: The Changing Meaning Of Left-rightmentioning
confidence: 99%
“…Using cross-lagged models, panel studies have supported both mechanisms by revealing that political identity is predicted by prior issue attitudes as well as vice versa (Carsey and Layman, 2006;Evans and Neundorf, 2013;Franklin, 1984;Goren, 2005;Highton and Kam, 2011;Johnston, 2006). Although most of these studies focused on partisanship, some studies demonstrated a similar mutual relation between left-right identification and issue attitudes (Jaeger, 2008;Pardos-Prado, 2011;Weber and Saris, 2014). All these studies were conducted on the major electoral panel studies that are available around the world (e.g., British Household Panel Study; National Election Study; Political Socialization Panel Study).…”
Section: Political Identity and Issue Attitudesmentioning
confidence: 98%